3D-QSAR Analysis of Acyl Sulfonamides and Acyl Sulfamides As AT1 Selective Angiotensin-II Receptor Antagonists Based on Semiemperical AM1 Calculations - BANCHHOR, MADHURI; BANCHHOR, PRAKASH; CHATURVEDI, S.C. (Asian Journal of Chemistry, 2010)
Considering the importance of developing AT1 selective Angiotensin-II receptor antagonists in management and treatment of hypertension, the present paper explores the selectivity requirements of acyl sulfonamides and acyl sulfamides for binding with AT1 receptor. The best triparametric equation derived for 25 compounds explains the importance of certain pharmacophoric features like lower unoccupied molecular orbital energy (ELUMO), Connolly accessible area(CAA) and Non-1, 4 vander Waals forces (VDW) for Angiotensin-II receptor antagonism. The statistically significant equation has been further validated by leave one out method.